230k views
3 votes
Can someone show me how to get the answer to this step by step? It's Combining Like Terms.
-9x^(2) - 7 +
4x +
10x^(2) - 14x

User Harish Raj
by
4.9k points

1 Answer

6 votes

Answer:

x² - 10x - 7

Explanation:

See steps below:

  • - 9x² - 7 + 4x + 10x² - 14x =
  • (-9x² + 10x²) + (4x - 14x) - 7 = ⇒ like terms combined in parenthesis
  • x² - 10x - 7 ⇒ simplified
User Rob Evans
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.